Sinonasal Teratocarcinosarcoma: A Rare Case Report - Bodhgire, Ashwini Sudhakar; Ganorkar, Shweta Dattakumar; Kulkarni, Anjali Sanjay (Annals of Pathology and Laboratory Medicine, 2025)
Background: Teratocarcinosarcoma is a type of malignancy that typically arises from germ cells. A teratocarcinoma in the nose would present as an unusual or rare clinical case, requiring imaging and biopsy for confirmation. It constitutes less than 1% of all cancers and approximately 3% of all malignancies of the head and neck region; only a few hundred cases have been reported worldwide. Because of its rarity, clinical presentation, and treatment challenges, it is essential to report and study cases of nasal teratocarcinoma. Case Presentation: We here report a case of Sinonasal Teratocarcinosarcoma (SNTCS), a 55-year-old female with a complaint of right-sided nasal blockage for over a month with a nasal bleed for one day. On local examination, there was swelling of the right alar region and dorsum with DNS to the left side and tenderness in all paranasal sinuses. There was no fogging on the right side. On anterior rhinoscopy, a chocolate-brown polypoidal mass obscuring the view of the floor, roof, cavity, and middle turbinate was seen. On histopathological examination, it was diagnosed as teratocarcinosarcoma of the nasal cavity. Immunohistochemistry confirmed the diagnosis. On follow-up, her condition deteriorated and she succumbed to death in the next 6 months. Conclusion: Teratocarcinosarcoma is a rare and aggressive sinonasal tumor with a hypothesized origin from somatic pluripotent stem cells of the nasal cavity. Its early diagnosis is important as it carries a poor prognosis.